The impact of chief executive officer narcissism on environmental, social, and governance reporting - Finja Lena Kind; Jennifer Zeppenfeld; Rainer Lueg (Business Strategy and the Environment, 2023)
We analyze the effect of chief executive officer (CEO) narcissism on environmental, social, and governance (ESG) reporting. The study relies partly on hand-collected, visual data and covers 57 German DAX 40 and MDAX companies from 2016 to 2020 (266 company-year observations, Bloomberg database). Looking into the sub-scores of ESG, CEO narcissism has a negative and linear relationship with environment and governance reporting but there is no significant relationship between narcissism and social reporting. Regression analyses further suggest a U-shaped (quadratic) relation between CEO narcissism and ESG reporting: while low to moderate degrees of narcissism affect overall ESG reporting negatively, as CEO levels of narcissism increase so does the level of reporting. Moreover, further analysis has shown that the quantity of reporting is additionally positively related to ESG performance. The study applies and validates a relatively new but easily applicable measure of narcissism and extends narcissism research in the area of curvilinear relationships. We offer several further implications for human resource managers, regulators, auditors, and (non-)financial analysts.
Keywords: 330; corporate social responsibility; environmental policy; stakeholder engagement; strategic decisions; sustainable development; upper echelons theory